Additional notes on South American Carex sect. Schiedeanae (Cyperaceae) and description of the new species Carex pachamamae - Jiménez-Mejías, P.; Reznicek, A. A. (Phytotaxa, 2018)
The revision of additional materials from MICH, MO, NY and US herbaria revealed interesting findings in Carex sect. Schiedeanae in South America. Carex pachamamae, a distinctive species from northern and central Bolivia is newly described and illustrated. The new species closely resembles C. subandrogyna, from southern Bolivia and northern Argentina, but it is distinguished from it by its leaves (pale bluish-green, subcoriaceous, usually with no lateral veins more prominent than the others adaxially, in C. pachamamae, vs. dark-green, herbaceous, with two conspicuously raised whitish lateral veins on the adaxial side more prominent than the rest in in C. subandrogyna) and utricle morphology (pale whitish-green, with the sides concave in C. pachamamae, vs. green to brownish below, with the sides convex in C. subandrogyna). Also, the first modern collections of C. lepida are presented, including the first reports of the species for Bolivia and Colombia, which implies a considerable expansion of the area of the taxon.